2008
DOI: 10.7589/0090-3558-44.4.946
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Tetracycline and Rabies Virus Antibody in Raccoons, Skunks, and Foxes Following Aerial Distribution of v-Rg Baits to Control Raccoon Rabies in Ontario, Canada

Abstract: More than 3.6 million baits containing a recombinant vaccinia virus-rabies glycoprotein (V-RG) oral rabies vaccine were aerially or hand-distributed during 1999-2006 in an approximate 4,000-9,000 km(2) area of eastern Ontario, Canada, as part of a multitactic approach to control the raccoon variant of rabies. The efficacy of the program was assessed through the collection and testing of > 6,900 animals for bait acceptance and rabies virus-specific antibodies. Raccoon acceptance of rabies vaccine baits was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…Variation in the number of baiting episodes among years; time-lags between bait distribution, bait uptake, and sample collection; raccoon population density, age structure (Linhart and Kennelly, 1967), and sex (Buyske et al, 1960); and condition and age of tetracycline within bait lots may be confounding. In Ontario, Rosatte et al (2008) found age effects in some, but not all, years for samples they studied, suggesting variation in this phenomenon within populations.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Variation in the number of baiting episodes among years; time-lags between bait distribution, bait uptake, and sample collection; raccoon population density, age structure (Linhart and Kennelly, 1967), and sex (Buyske et al, 1960); and condition and age of tetracycline within bait lots may be confounding. In Ontario, Rosatte et al (2008) found age effects in some, but not all, years for samples they studied, suggesting variation in this phenomenon within populations.…”
Section: Discussionmentioning
confidence: 84%
“…Tetracycline hydrochloride (tetracycline) is a commonly used compound for this purpose, and is detectable 2-5 days postconsumption (Hanlon et al, 1989) by ultraviolet microscopy of crosssectioned teeth . Consequently, tetracycline has an extensive history of use in oral vaccination and predator control (Linhart and Kenelly, 1967;Hanlon et al, 1989;Bachmann et al, 1990;Hable et al, 1992;Creekmore et al, 1994;Farry et al, 1998;Johnston et al, 2005;Slate et al, 2005;Ramey et al, 2008;Rosatte et al, 2008). More specifically, tetracycline has been used to assess bait uptake as part of oral vaccination campaigns and research in red foxes (Vulpes vulpes; Johnston and Voight, 1982;Niin et al, 2008), striped skunks (Mephitis mephitis; Johnston and Voight, 1982), raccoons (Procyon lotor; Rupprecht et al, 1987;Rosatte et al, 2009), coyotes (Canis latrans; Linhart and Kinelly, 1967), raccoon dogs (Nyctereutes procyonoides; Niin et al, 2008), and feral swine (Sus scrofa; Campbell et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the number of rabies cases has rapidly decreased in all three Baltic States since 2006; for instance, rabies has been nearly eradicated in Estonia since summer 2009 (Cliquet et al 2012). Levels of the TTC marker during the different ORV seasons were comparable for spring and autumn campaigns, and showed an increasing tendency (7-28%) throughout the period studied, suggesting a cumulative exposure to distributed baits (Rosatte et al 2008). Juvenile red foxes appeared to have lesser access to baits, which confirms earlier studies with similar results (Rosatte and Lawson 2001).…”
Section: Discussionmentioning
confidence: 86%
“…While vaccines are often among the tools available to wildlife managers (Wobeser ); e.g., raccoon rabies variant (Rosatte et al. ), tuberculosis (Tompkins et al. ), brucellosis (Cross et al.…”
Section: Challenges and Future Opportunitiesmentioning
confidence: 99%
“…Vaccines selecting for increased virulence have important evolutionary implications for malaria (Mackinnon et al 2008) and human papilloma virus vaccination programs (Stearns 2012). While vaccines are often among the tools available to wildlife managers (Wobeser 2002); e.g., raccoon rabies variant (Rosatte et al 2008), tuberculosis (Tompkins et al 2013), brucellosis , their impermanence, and their role as selective agents are rarely considered.…”
Section: Challenges and Future Opportunitiesmentioning
confidence: 99%